Advancing Voltage Control of Renewable Energy Resources Through a Transformerless Dc/Dc Converter: Enhancing Voltage Ratio and Efficiency - Sabzalian , M (Springer Nature, 2024)
In the realm of renewable energy utilization, the effective harnessing of low voltage sources necessitates the application of specialized interfaces like DC–DC power converters. Within this framework, step-up DC–DC power converters play a crucial and central role in enabling the efficient harvesting of renewable energy. This research presents an innovative DC–DC power converter with a high voltage transfer ratio, eliminating the need for a transformer. The converter utilizes switched inductor and capacitor techniques, demonstrating its unique advantages compared to traditional designs. Emphasizing low voltage switch stress as a technical priority, the proposed converter demonstrates a symbiotic relationship between high step-up voltage ratio and reduced power losses. Both continuous and discontinuous operating modes are examined to elucidate the steady-state behavior of the 250 W implemented prototype. The study provides comprehensive insights into the converter s capabilities, which are subsequently verified through meticulous experimental validation. The presented prototype exhibits impressive efficiency, reaching 97.1% owing to its ability to maintain low voltage switch stress during nominal operation. By effectively addressing the problem of low voltage renewable energy utilization, this research contributes to the advancement of sustainable power generation technologies. © King Fahd University of Petroleum & Minerals 2023.